Risk Aversion and Incentive Effects: Comment - Harrison, Glenn W; Johnson, Eric; Mcinnes, Melayne M; Rutström, E. Elisabet (American Economic Review, 2005)
Risk Aversion and Incentive Effects: Comment by Glenn W. Harrison, Eric Johnson, Melayne M. McInnes and E. Elisabet Rutström. Published in volume 95, issue 3, pages 897-901 of American Economic Review, June 2005